(untitled) (Web of Teachers: Inderscience Research, 2025)
The Uzbek language, with its rich culture and historical heritage, is considered interesting and useful for learning for foreigners. Today, due to the processes of globalization and the development of information technologies, the opportunities for foreigners to use modern technologies for teaching the Uzbek language expand. In this article we will consider the importance of modern technologies in the teaching of Uzbek language to foreigners, their advantages and their application.